Gotta Catch All the Trading Cards - Abdo, Kenny 1986 (Minneapolis, Minnesota Fly!, 2024)
"This title looks at the Pokemon Trading Card Game and gives information related to its release, its rise in popularity, and the way it has changed tabletop games forever"--Amazon.
Includes index.
113583
Keywords: Pokemon (Fictitious characters); Trading cards; Collectible card games; Pokemon (Game); High interest-low vocabulary books